Phonons on Cu(001) surface covered by submonolayer alkali metals. (29th January 2019) - Borisova, S D; Rusina, G G; Eremeev, S V; Chulkov, E V
Abstract: We present a theoretical investigation of the structural and vibrational properties of ordered 2D phases formed by the Li, Na and K atoms on the Cu surface. The lattice relaxation, phonon dispersions and polarization of vibrational modes as well as the local density of states are calculated using the embedded-atom method. The obtained structural parameters and vibrational frequencies are in close agreement with available experimental results.